Efficient electrocatalytic oxygen evolution by Fe3C nanosheets perpendicularly grown on 3D Ni foams. (21st June 2019) - Zhu, Shasha; Lei, Jinglei; Zhang, Lina; Lu, Lijuan
Abstract: The development of efficient and earth-abundant catalyst for the oxygen evolution reaction (OER) is an important challenge for the renewable energy research community. Here, we report a facile method to design a nanosheet-like structure of Fe3 C, perpendicularly grown on Ni foam (NF) as a catalyst for OER by hydrothermal reaction and annealing treatment at a low temperature. The synthesized Fe3 C has good conductivity, small charge transfer resistance (Rct ), high active site density, and excellent stability, which make it highly efficient OER catalyst. Fe3 C/NF has a low overpotential of 262 mV at a current density of 10 mA cm −2 and a small Tafel slope of 49 mV dec −1 . Remarkably, Fe3 C/NF also has good electrochemical stability, which helps maintain its activity in 1.0 M KOH solution for at least 100 h. Therefore, the simple method to prepare perpendicularly grown Fe3 C on a NF substrate can enhance the OER properties, which make Fe3 C/NF a promising material for replacing noble metal-based catalysts for OER applications. Highlights: Fe3 C/NF material are synthesized by a facile method. The sheet-like structure promotes more active sites. The overpotential of Fe3 C/NF at the current density of 10 mA cm –2 is 262 mV. Fe3 C/NF exhibits high OER activity surpassing that of IrO2 . Fe3 C/NF surface has superaerophobic property.